My sun printed archive is blue - Van der Merwe, Petronella (Centre for Film and Media Studies, 2026)
I'm a white Afrikaner. I am spun from a villainous history - a vestige signifying coloniality. I have inherited a colonial archive that documents my ancestor's journey as a Rhenish missionary from Germany to Namibia in the year 1863. From a contemporary present that is framed by post-colonial and postcolonial discourse, colonial archives warrant verwerking/ alteration/ processing/ working and reworking. Framed by practice-led research, this study uncovers how I can verwerk my colonial archive through performance to incite transgression of preservation, to move beyond the ossification of colonial heirlooms (my archive) to reconcile with emerging post-colonial futures. In my performance, I transform my colonial archive into tactile textile - linen. Linen, in its entirety as ‘text embedded tapestries' symbolises narratives, history and the past, all woven together to form what constitutes the present. The word ‘lineage' originates from the noun ‘line'. The word ‘line' in turn, etymologically stems from the term lino meaning linen - the flax seed fabric (Miller 2005: 239). A single thread can therefore signify themes of genealogy, heritage, identity and ancestry (van der Merwe 2022: 2). I am interested in modes of reworking and reimagining my colonial archive. I perform acts such as tainting, tearing, ripping, (re)stitching and untangling large tapestries of linen - embodying a scrutiny of my white colonial archive. In my performance research I demonstrate a ‘grappling with' my colonial past from my contended post-colonial present. I ‘taint', ‘scratch' and make marks - as I attempt to insert new perspectives and self-reflective insight. Incited by my performance research, I uncovered the notion of poisoning and the image of a moth as two potent concepts in relation to the notion of verwerking . In relation to the linen, a moth has the capacity to devour, consume and process material (established as a metaphor for my archival text). The moth is me, devouring and processing my colonial text. Secondly, I taint the white, bleached linen using cyano-type printing that results in mournful, sickly blue stains and blotches smeared across the once white tapestries - signifying alteration and transgression of preservation. It can be stated that I poison my colonial text. From the poison emerges remedy and an attempt to reconcile with the past. I unpack the notion of poison alongside Jacques Derrida's (1998) concept of pharmakon (poison as remedy). These alterations and indiscretions to my colonial archive and it's text offer emergence, allowing my ossified colonial archive to evolve beyond a preserved state. For me, my explication and performance research can ultimately become a new chapter in my family's archive that reflects on a past that is interwoven and entangled up within villainous history - that warrants acknowledgement and critical reflection.